Application of Geogebra Learning Media to Increase Class IX Students' Learning Motivation on Geometry Transformation Material at SMP Negeri 1 Kisaran - Adyva, Vieka; Syafitri, Ely; Sirait, Lusi (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
Motivation to learn is important so that students can undergo the learning process well. So, it is necessary to implement good learning media to help increase student learning motivation. The learning media applied in this research is the Geogebra application because of its suitability for geometric transformation material. This research was carried out to increase the learning motivation of class IX students through the application of geogebra learning media at SMP Negeri 1 Kisaran. Researchers collected data using quantitative descriptive methods. Research instruments include direct interviews with teachers and students, as well as online questionnaires via Google Form. Students who are involved in learning with Geogebra show a higher level of participation and are more enthusiastic in learning geometric transformation material. Apart from that, they also achieved higher concept understanding test results than students who studied conventionally. This research provides an important contribution in supporting the use of technology in mathematics learning, especially in the context of geometric transformations, and provides recommendations for teachers and educational policy makers to expand the use of technology-based learning media in the learning process